2017
DOI: 10.1212/wnl.0000000000004058
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of dementia with Lewy bodies

Abstract: The Dementia with Lewy Bodies (DLB) Consortium has refined its recommendations about the clinical and pathologic diagnosis of DLB, updating the previous report, which has been in widespread use for the last decade. The revised DLB consensus criteria now distinguish clearly between clinical features and diagnostic biomarkers, and give guidance about optimal methods to establish and interpret these. Substantial new information has been incorporated about previously reported aspects of DLB, with increased diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
1,044
1
21

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 3,129 publications
(1,112 citation statements)
references
References 60 publications
18
1,044
1
21
Order By: Relevance
“…The patients with clinical diagnosis of AD predominantly presented with amnestic features, with impairment in other nonmemory domains. All DLB patients met criteria for probable DLB based on the third and fourth consensus criteria5, 11 (i.e., all patients had at least two of the core clinical features, but 123 I‐FP‐CIT SPECT was not used for diagnosis). Patients who were diagnosed with DLB exhibited visuospatial and executive dysfunction in addition to memory impairment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients with clinical diagnosis of AD predominantly presented with amnestic features, with impairment in other nonmemory domains. All DLB patients met criteria for probable DLB based on the third and fourth consensus criteria5, 11 (i.e., all patients had at least two of the core clinical features, but 123 I‐FP‐CIT SPECT was not used for diagnosis). Patients who were diagnosed with DLB exhibited visuospatial and executive dysfunction in addition to memory impairment.…”
Section: Resultsmentioning
confidence: 99%
“…These patients had been followed longitudinally until death or until they were no longer able to participate in the research program between August 2003 and May 2016. Consensus clinical diagnosis of a dementia type, including Alzheimer's disease dementia (ADem),9, 10 DLB,5, 11 primary progressive aphasia (PPA)/frontotemporal lobar degeneration (FTLD),12, 13 and corticobasal syndrome (CBS)14, 15 was made based on previously published criteria. Rapid eye movement (REM) sleep behavior disorder (RBD) was diagnosed based on clinical +/− polysomnographic features 16…”
Section: Methodsmentioning
confidence: 99%
“…Its main clinical characteristics, along with the dementia, are cognitive and vigilance fluctuations, recurrent and detailed visual hallucinations, and spontaneous features of parkinsonism [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that both visuoperceptual and visuospatial functions are particularly impaired in DLB patients. Indeed, 70–80% of DLB patients experience frequent visual hallucinations [2-4], which are one of the core diagnostic criteria of the disease. Regarding visuospatial abilities, these patients show a more severe deficit than Alzheimer disease (AD) patients in shape copying tasks [5], and this deficit already exists in the mild cognitive impairment stage [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Control participants had an MMSE ≥26 and no signs of dementia or mild cognitive impairment. DLB patients were recruited prior to the publication of the 2017 diagnostic criteria for DLB,6 but by definition, they would all satisfy the updated criteria for probable DLB.…”
Section: Methodsmentioning
confidence: 99%